Formulation and Characterization Profile of Sugarcane (Saccharum officinarum L.) Leaf Extract Emulsion - Sishartami, Lintang Widya; Weningtyas, Anditri; Ariesaka, Kiky Martha; Wiratama, Arif Ladika; Wibisono, Taurisma Aulia Nanda (Jurnal Biologi Tropis, 2025)
Sugarcane (Saccharum officinarum L.) leaves contain various bioactive compounds, which exhibit antioxidant and pharmacological potential. However, their application in pharmaceutical preparations faces challenges due to low solubility, stability, and bioavailability. Therefore, the development of an emulsion formulation is needed to improve its stability and absorption. This study aims to determine the phytochemical content of sugarcane leaf extract and to evaluate the physical stability of its emulsion formulation. The extraction was obtained through maceration using 96% ethanol, followed by phytochemical screening. Emulsions were prepared using sugarcane leaf extract as the active ingredient, Virgin Coconut Oil (VCO) as the oil phase, Tween 80 as a surfactant, and PEG 400 as a co-surfactant. The formulations were tested for organoleptic properties, emulsion type, percent transmittance, pH, particle size, polydispersity index, zeta potential, centrifugation, and cycling stability. The results showed that sugarcane leaf extract contained flavonoids, alkaloids, tannins, phenols, triterpenoids, and saponins. Among the four tested formulas, F1 and F2 showed the best stability, with pH 6–7, high percent transmittance, uniform particle size with polydispersity index <0.3, and absence of phase separation. These findings suggest that F1 and F2 represent optimal emulsion formulations for further pharmaceutical development.